Orientaciones astronómicas en la arquitectura de Mesoamérica: Occidente y Norte - Francisco Sánchez Nava, Pedro (Prostor, kraj, čas, 2016)
This monograph presents the results of a study of orientations in prehispanic architecture of western and northern Mesoamerica. Analyzing the alignment data collected with field measurements for a number of civic and ceremonial buildings at 21 archaeological sites, we have been able to conclude that they were largely oriented on astronomical grounds. Since the study area is extensive and culturally diverse, while the data sample is relatively small, the orientations that have been analyzed exhibit considerable variability.